1996
DOI: 10.1093/intimm/8.6.877
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γis a potent inducer of Ig secretion by sort-purified murine B cella activated through the mlg, but not the CD40,signaling pathway

Abstract: IFN-gamma has been shown to either stimulate or inhibit Ig secretion. No studies have yet addressed the basis for these seemingly conflicting properties nor whether IFN-gamma acted directly at the level of the B cell to mediate its effects. Thus, we studied the ability of IFN-gamma to regulate Ig secretion in sort-purified, resting murine B cells that were >99% Ig+, activated either through membrane Ig using unconjugated or dextran-conjugated anti-IgD antibodies (alphadelta-dex) or through CD40 using soluble o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 49 publications
0
35
0
1
Order By: Relevance
“…One explanation for the difference is that Snapper et al (31) use resting B cells, and some activation in our B cell preparation may allow secretion by cells cultured in CD40L ϩ IFN-␥. Another explanation is that our CD40L on Sf21 cells might result in different or more potent signaling through CD40 than does the membrane preparation used by Snapper et al (31).…”
Section: Discussionmentioning
confidence: 92%
“…One explanation for the difference is that Snapper et al (31) use resting B cells, and some activation in our B cell preparation may allow secretion by cells cultured in CD40L ϩ IFN-␥. Another explanation is that our CD40L on Sf21 cells might result in different or more potent signaling through CD40 than does the membrane preparation used by Snapper et al (31).…”
Section: Discussionmentioning
confidence: 92%
“…Previous reports have demonstrated that B cells stimulated via CD40 were extremely sensitive to Fas-mediated apoptosis, whereas dual ligation of CD40 and surface Ag receptors made them resistant (50,51). In B cells activated through LPS or CD40 stimulation, IFN-␥ inhibits Ab secretion in the absence of surface Ig stimulation, but induces Ab secretion in the presence of surface Ig stimulation (52)(53)(54)(55). These previous data are consistent with our current findings, in that neutralization of IFN-␥ activity as well as blockade of B cell apoptosis are required to increase IgM production in cultures with high dose Ag (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 is well recognized as a factor acting on B cells to induce Ig secretion (44), and the production of IL-6 by B cells infected in vitro with ␥HV68 (43) suggests a role for the cytokine as a virus-induced autocrine growth factor. IFN-␥ induces Ig production by activated B cells (45) and is also the major cytokine promoting class switching to IgG2a (46). These functions suggest a significant role for IFN-␥ in the vigorous, IgG2a-biased, nonspecific Ab response associated with ␥HV68 infection.…”
Section: Nonspecific Ab Production In Cytokine-deficient Micementioning
confidence: 94%